THE ROLE OF SCAFFOLDING STRATEGIES IN IMPROVING STUDENTS’ READING SKILLS: THE ROLE OF SCAFFOLDING STRATEGIES IN IMPROVING STUDENTS’ READING SKILLS - Arazdurdiyeva, Annasoltan (Журнал иностранных языков и лингвистики, 2025)
Reading is a foundational skill that serves as the gateway to academic success and lifelong learning. In educational settings, the development of strong reading skills is crucial for enabling students to access, process, and analyze information effectively. However, for many students—particularly those in early learning stages or with diverse language backgrounds—reading presents a significant challenge. This has prompted educators to seek out instructional strategies that can make reading more accessible and engaging. Among these, scaffolding has emerged as a powerful pedagogical approach. The concept of scaffolding originates from Lev Vygotsky’s theory of the Zone of Proximal Development (ZPD), which posits that learners can achieve higher levels of understanding with the guidance of a more knowledgeable other. Scaffolding builds on this idea by providing structured support tailored to a student’s current level of understanding, enabling them to perform tasks they could not complete independently. As the learner’s competence grows, the support is gradually withdrawn, fostering independence and confidence.